2013
DOI: 10.1007/s12105-013-0429-0
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking MASC: Bringing to Light the Unique Morphologic, Immunohistochemical and Genetic Features of the Newly Recognized Mammary Analogue Secretory Carcinoma of Salivary Glands

Abstract: Mammary analogue secretory carcinoma (MASC) is a recently described salivary gland neoplasm that is characterized by its striking morphologic and molecular similarities to secretory carcinoma of the breast. This review highlights the characteristic clinical, histologic, immunophenotypic, and molecular features of MASC, and draws attention to the differential diagnosis of this increasingly recognized tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
145
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(153 citation statements)
references
References 25 publications
(94 reference statements)
6
145
2
Order By: Relevance
“…These tumors were termed mammary analogue secretory carcinomas (MASC). Since this initial report, there have been approximately 100 additional cases published [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. These have been previously diagnosed as unusual variants of acinic cell carcinoma, adenoid cystic carcinoma, cystadenocarcinoma, mucoepidermoid carcinoma or adenocarcinoma, NOS.…”
Section: Mammary Analogue Secretory Carcinoma Of the Salivary Glandsmentioning
confidence: 99%
See 1 more Smart Citation
“…These tumors were termed mammary analogue secretory carcinomas (MASC). Since this initial report, there have been approximately 100 additional cases published [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. These have been previously diagnosed as unusual variants of acinic cell carcinoma, adenoid cystic carcinoma, cystadenocarcinoma, mucoepidermoid carcinoma or adenocarcinoma, NOS.…”
Section: Mammary Analogue Secretory Carcinoma Of the Salivary Glandsmentioning
confidence: 99%
“…The proliferative rate ranges from 5 to 28 % [20]. Several recent studies demonstrated that the combination of S100, mammoglobin and especially large vacuole adipophilin staining is very helpful to eliminate almost all of the other differential diagnostic mimics of mammary analogue secretory carcinoma [24,27,30,39]. This latter stain is important, as occasionally mammoglobin, similar to acinic cell carcinoma, is only focally positive in MASC.…”
Section: Mammary Analogue Secretory Carcinoma Of the Salivary Glandsmentioning
confidence: 99%
“…Mammary analog secretory carcinoma expresses mammaglobin, GATA3 and variably expresses gross cystic disease fluid protein-15 (GCDFP-15) similarly to many primary breast carcinomas. Other antigens expressed include S-100 protein (diffuse in most cases), vimentin and high molecular weight keratins with variable expression reported for p63 [1,[3][4][5][6][7]. In their original description of MASC, Skalova and colleagues found an ETV6-NTRK3 fusion in all cases [1].…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Mitotic rates are usually 0 -1 mitotic figures/10 high-powered fields. [12] Immunohistochemical studies show positive staining with vimentin, mammaglobin, cytokeratin 7 and S-100 protein. [3,8] Mammaglobin and S-100 protein can also be positive in polymorphous lowgrade adenocarcinomas and some adenoid cystic carcinomas.…”
Section: Discussionmentioning
confidence: 97%